Utility of Ultrasonography of the Median Nerve With a High‐Frequency Probe for the Diagnosis of Dialysis‐Related Carpal Tunnel Syndrome. Issue 5 (17th March 2016) - Yamazaki, Tadashi; Kawahara, Naomi; Arai, Kazunori; Oyoshi, Koji; Oshima, Masami; Koike, Sachiko; Miyauchi, Akiko; Hayasaka, Tokie; Saito, Tetsuo; Tsuruoka, Shuichi
Abstract: This cross‐sectional study aimed to determine the utility of ultrasonography with improved resolution using a high‐frequency probe for dialysis‐related carpal tunnel syndrome (CTS). This study targeted 125 hemodialysis patients at our hospital. A 12 MHz probe was placed on the carpal tunnel area to identify the median nerve. The compression rate of the nerve was calculated by measuring the smallest diameter of the compressed nerve and largest diameter of the unaffected part. To quantify CTS symptoms, we determined the presence of Tinel's sign, measured pinch strength, and used questionnaires to assess numbness and pain. The association of these clinical data with the compression rate was examined. Mean compression rate was 12.1 ± 1.1%. The compression rate cutoff value for those positive with Tinel's sign was 25%, (sensitivity and specificity were 0.80 and 0.91, respectively), and that for those with a history of CTS surgery was 25% (sensitivity and specificity were 0.67 and 0.89, respectively). Multiple regression analysis identified duration of dialysis, β2‐microglobulin(β2‐Mg) concentration, positivity for Tinel's sign, history of CTS surgery, and pinch strength as independent compression rate determinants. Notably, compression rates were significantly higher in patients with a ≥4‐year duration of dialysis and a β2‐Mg level of 20 mg/L or more. The compression rate of the median nerve measured by an improved ultrasound device significantly correlated with clinical symptoms, medical history, and serological features associated with dialysis‐related CTS. Because ultrasonography is non‐invasive, the examination might be a simple method especially for early diagnosis of dialysis‐related CTS.